2018
DOI: 10.1007/s13313-018-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of site, weather and Phytophthora cinnamomi in the decline and death of Eucalyptus marginata – jarrah dieback investigations in the 1970s to 1990s

Abstract: Relative importance of site, weather and Phytophthora cinnamomi in the decline and death of Eucalyptus marginatajarrah dieback investigations in the 1970s to 1990s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…However, our results are similar to Turco et al [36], who observed no symptoms in Quercus ilex and Q. cerris that were inoculated by P. cinnamomi in a full irrigation treatment, although root necrosis was eventually observed after 11 weeks. The occurrence of secondary symptoms following the P. cinnamomi infection might be latent depending on the pathogen aggressiveness, host susceptibility and environmental condition [22,61]. A time lag of 6 to 18 months can occur during Phytophthora infection until drought-like symptoms are observed in field studies [22,35,61].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, our results are similar to Turco et al [36], who observed no symptoms in Quercus ilex and Q. cerris that were inoculated by P. cinnamomi in a full irrigation treatment, although root necrosis was eventually observed after 11 weeks. The occurrence of secondary symptoms following the P. cinnamomi infection might be latent depending on the pathogen aggressiveness, host susceptibility and environmental condition [22,61]. A time lag of 6 to 18 months can occur during Phytophthora infection until drought-like symptoms are observed in field studies [22,35,61].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of secondary symptoms following the P. cinnamomi infection might be latent depending on the pathogen aggressiveness, host susceptibility and environmental condition [22,61]. A time lag of 6 to 18 months can occur during Phytophthora infection until drought-like symptoms are observed in field studies [22,35,61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While marri has not been targeted for intensive logging, the species has been affected by the logging of neighbouring jarrah trees and subsequent effects on hydrology. Despite their co-occurrence with jarrah, there are no records of mass marri deaths alongside jarrah, and many marri typically continued to survive where mass jarrah deaths occurred, with few deaths observed along infestation fronts (Davison, 2015(Davison, , 2018Shearer & Tippett, 1989).…”
Section: Introductionmentioning
confidence: 99%